Dopamine metabolite levels in the vitreous of diabetic and non-diabetic humans. (June 2020) - Hendrick, Andrew; Smith, Jesse; Stelton, Chris; Barb, Scott; Yan, Jiong; Cribbs, Blaine; Jain, Nieraj; Yeh, Steve; Hubbard, G. Baker; He, Li; Dhakal, Susov; Iuvone, P. Michael
Abstract: Animal studies suggest that the retinal dysfunction in diabetic subjects that precedes overt clinical vasculopathy may be due to a retinal dopamine deficit. We analyzed levels of dopamine (DA) and its primary metabolite, 3, 4-dihydroxyphenylacetic acid (DOPAC), in the vitreous of diabetic and non-diabetic human subjects. Adult patients undergoing pars plana vitrectomy for non-hemorrhagic indications were prospectively recruited from the Emory Eye Center in Atlanta, GA. Vitreous samples were analyzed using high performance liquid chromatography (HPLC) to measure levels of DOPAC and DA in the vitreous specimens. Vitreous samples from 9 diabetic patients and 20 from non-diabetic patients were analyzed. No eyes had apparent diabetic retinopathy. Mean normalized DA concentration in vitreous of diabetic subjects was 0.76 ± 0.12 pg/μL vs . 0.73 ± 0.08 pg/μL in non-diabetic vitreous (p = 0.849). DOPAC concentration was 8.84 ± 0.74 pg/μL in vitreous of diabetic subjects vs. 9.22 ± 0.56 pg/μL in vitreous of non-diabetic subjects (p = 0.691). No difference was observed in the concentrations of DA and DOPAC in the vitreous of people without diabetes compared to those with diabetes without retinopathy. Highlights: Animal models of diabetes mellitus (DM) indicate that deficits in retinal dopamine precede vascular dysfunction and contribute to compromised visual function. Levels of dopamine and 3, 4-dihydroxyphenylacetic acid (DOPAC) in vitreous of human subjects were analyzed. No statistically significant differences in dopamine or DOPAC levels were found between samples from type II DM subjects and non-diabetic subjects.